Do Natural Resource Revenues Hinder Financial Development? The Role of Political Institutions - Sambit Bhattacharyya; Roland Hodler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We theoretically and empirically examine the relationship between natural resource revenues and financial development. In the theoretical part, we present a politico-economic model in which contract enforcement is low and decreasing in resource revenues when political institutions are poor, but high otherwise. As poor contract enforcement leads to low financial development, the model predicts that resource revenues hinder financial development in countries with poor political institutions, but not in countries with comparatively better political institutions. We test our theoretical predictions systematically using panel data covering the period 1970 to 2005 and 133 countries. Our estimates confirm our theoretical predictions. Our main results hold when we control country fixed effects, time varying common shocks, income and various additional covariates. They are also robust to alternative estimation techniques, various alternative measures of financial development and political institutions, as well as across different samples and data frequencies. We present further evidence using panel data covering the period 1870 to 1940 and 31 countries.
Keywords: D7; O1; 330; Natural resources; political institutions; financial development